2018
DOI: 10.1002/fee.1823
|View full text |Cite
|
Sign up to set email alerts
|

Basin‐scale effects of small hydropower on biodiversity dynamics

Abstract: Construction of small hydropower plants (<10 megawatts) is booming worldwide, exacerbating ongoing habitat fragmentation and degradation, and further fueling biodiversity loss. A systematic approach for selecting hydropower sites within river networks may help to minimize the detrimental effects of small hydropower on biodiversity. In addition, a better understanding of reach‐ and basin‐scale impacts is key for designing planning tools. We synthesize the available information about (1) reach‐scale and (2) basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…The above mentioned ecological impacts are mainly studied during and immediately after the construction of large dams. In comparison, the potential ecological impacts due to the presence of small hydropower plants are less considered and very few studies assess ways to mitigate their effects (Sutherland et al, 2020); this situation can be problematic because there is a major increase in support of these smaller infrastructures (Couto and Olden, 2018;Lange et al, 2018;Muller, 2019). The definition of small hydropower plants vary immensely from country to country and broadly refers to facilities that produce less electricity and operate in smaller rivers as compared to large hydropower plants (Couto and Olden, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above mentioned ecological impacts are mainly studied during and immediately after the construction of large dams. In comparison, the potential ecological impacts due to the presence of small hydropower plants are less considered and very few studies assess ways to mitigate their effects (Sutherland et al, 2020); this situation can be problematic because there is a major increase in support of these smaller infrastructures (Couto and Olden, 2018;Lange et al, 2018;Muller, 2019). The definition of small hydropower plants vary immensely from country to country and broadly refers to facilities that produce less electricity and operate in smaller rivers as compared to large hydropower plants (Couto and Olden, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, small hydropower plants have a myriad of operation modes, flow control structures, and environmental impacts, turning the definition very ambiguous. In this study we consider a small hydropower plant an installation with b10 MW of generation capacity (Couto and Olden, 2018;Lange et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, more than 82,000 SHPs have been constructed worldwide, and an additional 10,569 SHPs are currently planned (Couto and Olden 2018), although this may be a substantial underestimate. However, despite their large numbers, SHPs contribute little to global hydropower production (Lange et al 2018). In the US, SHPs account for 65% of the country's 2,320 hydropower facilities but provide only 3.5% of the generating capacity (Sharma et al 2019).…”
Section: Small Hydropower Goes Uncheckedmentioning
confidence: 99%
“…the medium of the other two definitions of connectivity, is almost always downstream but can take place as exchanges laterally (with the banks), longitudinally (through the network), into the hyporheic zone or groundwater, and evolve temporally (Ward, 1989). Connectivity has significant implications for flood generation, sediment production, and aquatic biodiversity among other management goals (Altermatt, 2013;Nadeau and Rains, 2007;Lange et al, 2018), however its usefulness of a concept is limited by a lack of coherence between all of its various definitions (Wohl et al, 2019). Further research on the connectivity indicated by eDNA is perhaps the solution to an metric that crosses disciplines and dimensions.…”
Section: Edna Is a Tracer For The Integrated Dimensions Of Hydrologicmentioning
confidence: 99%